2021
DOI: 10.1074/jbc.ra120.016210
|View full text |Cite
|
Sign up to set email alerts
|

The X-linked intellectual disability gene product and E3 ubiquitin ligase KLHL15 degrades doublecortin proteins to constrain neuronal dendritogenesis

Abstract: Proper brain development and function requires finely controlled mechanisms for protein turnover and disruption of genes involved in proteostasis is a common cause of neurodevelopmental disorders. Kelch-like 15 (KLHL15) is a substrate adaptor for cullin3 (Cul3)-containing E3 ubiquitin ligases and KLHL15 gene mutations were recently described as a cause of severe X-linked intellectual disability (XLID). Here, we used a bioinformatics approach to identify a family of neuronal microtubule-associated proteins (MAP… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 67 publications
(78 reference statements)
0
8
0
Order By: Relevance
“… 27 , 28 , 29 , 30 The stability of Dcx is post-translationally regulated by UPS, which is mediated by E3 ligases, including CRL3 and Mdm2. 13 , 31 Therefore, we hypothesized that CRL4 might also control Dcx stability. Through immunoblotting following immunoprecipitation, we confirmed that a small fraction of Dcx interacts with Cul4a and Cul4b in DIV4 neurons ( Figure 8 A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 27 , 28 , 29 , 30 The stability of Dcx is post-translationally regulated by UPS, which is mediated by E3 ligases, including CRL3 and Mdm2. 13 , 31 Therefore, we hypothesized that CRL4 might also control Dcx stability. Through immunoblotting following immunoprecipitation, we confirmed that a small fraction of Dcx interacts with Cul4a and Cul4b in DIV4 neurons ( Figure 8 A).…”
Section: Resultsmentioning
confidence: 99%
“… 11 , 12 Similarly, Kelch-like 15 (Klhl15), a substrate adaptor for CRL3 implicated in X-linked intellectual disability, promotes destabilization of the Dcx protein, thereby inhibiting dendrite outgrowth. 13 Mutations in human CUL4B , which encodes cullin 4b in CRL4, are also linked to X-linked intellectual disability. 14 , 15 Cul4b knockout mice exhibit spatial learning defects and epileptic hypersensitivity with abnormal dendritic morphology in the interneurons of the hippocampus.…”
Section: Introductionmentioning
confidence: 99%
“…Mdm2 restricts the level of Dcx via the ubiquitinationproteasome degradation system, thereby inhibiting dendritic spine morphogenesis in olfactory bulb interneurons 32 . Klhl15-CRL3 complex targets Dcx, resulting in restriction of neuritogenesis 12 . This implies that CRL3 and CRL4 may share substrates and have overlapping functions in neuritogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been well-known that Dcx facilitates axon and dendrite morphogenesis during neurodevelopment by stabilizing microtubules and regulating actin laments [28][29][30][31] . And Dcx protein is post-translationally regulated by the ubiquitination-proteasome system mediated by CRL3 or Mdm2 E3 ligase 12,32 . Therefore, we postulated that CRL4 may also control stability of Dcx among the CRL4-interacting proteins.…”
Section: Crl4-crbn Complex Controls the Stability Of DCX Proteinmentioning
confidence: 99%
See 1 more Smart Citation